4. EVALUATION OF THE RESULTS OF WOUND CARE AFTER SKIN GRAFT SURGERY FOR SKIN CANCER AT THE DEPARTMENT OF MUSCULOSKELETAL SURGERY, K HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: Comments on the results of skin grafting wound care after skin cancer surgery at the Department of Orthopedic Surgery.Materials and methods: Cross-sectional descriptive study on 62 skin cancer patients who underwent skin grafting surgery. Study subjects had records of treatment and follow-up care with full evaluation.Results: Patients had 100% wound healing results at the donor site, 25.8% complications at the graft site. Postoperative flap grafts achieved "Good" results after 1 week at 54.9% - after 1 month at 56.5%.Conclusion: The study showed that the rate of patients with good treatment results and improvement gradually increased from the first week after surgery until discharge from the hospital, reaching 85.48%.